PENGARUH PEMBERIAN DADIH DENGAN PERUBAHAN JUMLAH Lactobacillus fermentum PADA FESES IBU HAMIL - Ranne Balqis (Universitas Baiturrahim, 2019)
Pregnant women with adequate prebiotic consumption known having better immune function and also better pregnancy, depress the event of premature labor and pre-eclampsia event. This study conducted to find out the influence of dadih consumption to the change of the number of lactobacillus fermetum in pregnant women. This study was a experimental study with equivalent pre-post test with control group design. Population of this study was those who included in join research with Dr. dr. Andani Eka putra, MSc and Dr. Helmizar, SKM, M.Biomed. We take population from pregnant women in 10 PUSKESMAS in Agam District, West Sumatera, with sampling was done consecutively. Minimal total sample was 24 for each group. After observation at the beginning of study, intervention group was given 100cc dadih daily until second observation. Mean of colony in pregnant women before taking dadih was 3,713 CFU/mh and after was 4,580 log CFU/g (p=0.367). In control group, the number of colony at 1st observation was 3,999 log CFU/g and 4,436 log CFU/g in 2 nd observation (p=0.475). The changes in both group were compared and resulting in significantly different change (p=0.022). There is no statistically significant influence of dadih consumption with the change in the number of lactobacillus fermentum in pregnant women. However, this study was found better change after observation in intervention group.